General health and livelihood status of emancipated (mukta) kamlahris of Nepal. - Neupane, Uttam (2012)
ABSTRACT: Kamlahri (young female domestic servants) is a form of bonded labour in which servants are bound to specific individuals or families to work off a debt incurred by them or by preceding generations. This system was prevalent in the western Terai of Nepal. A cross sectional study was conducted among randomly selected 452 emancipated Kamlahris in Dang district. Data were collected using pre tested questionnaire by direct interviews, focus group discussion, key informant interviews and taking anthropometric measurements. Since the Kamlahris were from poor community hosing condition was very disgraceful. Mobile phone and bicycle were most commonly available amenities whereas hen, cock and or duck were most prevalent livestocks. Less than half of emancipated Kamlahris were involved in income generating activities, however; their income was very low. About 71 percent had their own land and 69 percent had share cropping land. Food was available for less than six months in half of the households. More than half of respondents' family member had taken loan in last one year. Emancipated Kamlahris who were studying had got monthly scholarship by government for ten months in a year. About one third of study population was enthusiastically participated in social activities. More than half of the respondents had faced at least one common health problem in last one month. Unfortunately, 96.5% were anemic with about 67% mildly anemic. No significant association is seen between hemoglobin level and age, religion, ethnicity, Type of family, Size of family, education, and BMI. However, statistically significant association was seen with health problems, involvement in social activities and place of residence. Surprisingly, about 50% had low Body Mass Index with 26% grade I and about 24% grade II thinness. BMI was significantly associated with age, ethnicity, size of family, education, participation in social activity, availability of own house, and psychological status. However, association between BMI and food availability within the home was not significant. About 6% mukta Kamlahri were psychologically ill. Furthermore, Age, loan of the family, location of residence, school enrollment, place of residence were and interest of back to Kamlahri were significantly associated with psychological status.